„Annehmen. Akzeptieren. Damit leben. Nicht vergessen. Sich erinnern.“ Subversive Erinnerungsverschiebungen der Post-Shoah-Generation in Mirna Funks Roman Winternähe (2015) - Rutka, Anna (Tematy i Konteksty, 2017)
The debut novel Winternähe by the young German-Jewish author Mirna Funk is a paradigmatic illustration of the post Shoah literature of the third, the grandchildren generation. The novel expounds on against background of the death of Shoah-survivors, the new ways of dealing with the family past and transnational Shoah memory in a complex relation to the globality and mobility as current conditions of the modern life. Funk’s novel also expounds on the subversive strategies, which are inherent in modern virtual communication media like Facebook or Instagram.